ECOFEMINIST ANALYSIS OF INDIAN FICTION WRITERS (International Journal of Food and Nutritional Sciences, 2022)
An analytical framework known as ecofeminism is one that investigates feminist ideologies and collectives with a particular focus on the protection of the environment. In her novel "Le Féminisme ou la Mort", which was published in 1974, the French author Francoise d'Eaubonne is generally credited as being the one who first popularized the word. According to ecofeminism, which is founded on the idea that women are inextricably linked to the natural world, there is a correlation between the deterioration of the environment and the oppression of women. According to ecofeminists, the link between women and the environment is proved by the existence of traditionally "female" qualities such as collaboration, caring, and aid. These characteristics are in common between women and the environment. In their work, ecofeminists seek to build linkages between many events, like menstruation and the moon, birth and creation, and other similar phenomena. Attempts are being made by the ecofeminist movement to rethink the conventional ideas that are associated with religion, politics, and the environment. It is the contention of ecofeminist theory that there is a substantial connection between the environmental crisis and the enslavement of women by patriarchal systems. The deeply engrained beliefs of patriarchy are called into question and disproved by this theory. The purpose of this article is to address the tendency that exists in society to neglect the unique connection that exists between women and the environment via the interactions that they have on a daily basis. As a result of their extensive competence in holistic and ecological awareness of the processes that occur in nature, the women who participate in subsistence economies are able to build wealth in conjunction with the environment. The novels A Riversutra (1993) by Gita Mehta, The God of Small Things (1997) by Arundhati Roy, The Madwoman of Jogare (1998) by Sohaila Abdulali, An Atlas of Impossible Longing (2008) by Anuradha Roy, and Monkey-Man (2010) by Usha K.R. are examples of novels that cover the entire spectrum of ecofeminism, from its beginnings to contemporary urban ecofeminism. This presentation will take a look at the literary works of these well-known authors from the point of view of ecofeminism by evaluating examples from activism and literature that prominently incorporate women, the purpose of this research is to investigate the historical development of ecofeminism in India. Recognizing the relevance of female authors and the great contributions they have made to the fields of literature and environmental studies is absolutely necessary in this day and age, when technological advancements are occurring at a rapid pace all over the world. In this article, the notion of ecofeminism and its several manifestations in India are investigated. It argues that women have a complicated connection with the environment, which challenges the conventional dichotomy between nature and civilization and places them in a position that is somewhere in the middle. There is a tremendous amount of attention placed on this specific facet by female authors who compose Indian literature in the English language. In order to give the backdrop for this study and illustrate the effect of the nature/culture dichotomy on concepts of gendered (environmental) citizenship, a short explanation of the dualism will be offered.